Open and Distance Learning in Early Childhood and Child Education: A Preliminary Systematic Mapping Review of Trends, Themes, and Research Gaps - Sulvia Fery Hanry Tondowala; Jacob Da Silva Araujo (Yayasan Adra Karima Hubbi, 2026)
Background. Open and distance learning has become increasingly significant in early childhood and child education, particularly following the rapid expansion of online and remote instruction during the COVID-19 pandemic. Nevertheless, research in this domain remains fragmented across diverse contexts, including early childhood education, primary education, teacher education, parental support, caregiver involvement, and child-focused digital learning services. Purpose. This study sought to provide a preliminary systematic mapping of publication trends, dominant themes, and research gaps in open and distance learning within early childhood and child education contexts. Method. A preliminary systematic mapping review was conducted, guided by the PRISMA 2020 reporting framework. Following screening and eligibility assessment, 18 studies were included in the final synthesis and analyzed descriptively and thematically. Results. Publications increased markedly during 2020 and 2021, reflecting the influence of pandemic-related school closures. Seven dominant themes emerged: online learning readiness, learner satisfaction and perception, tutorial and pedagogical quality, teacher or tutor competence, institutional support, parental and caregiver involvement, and child-focused digital learning support. The findings indicate that young children's digital learning requires adult mediation, age-appropriate instructional design, institutional readiness, and sustained school–home collaboration. Conclusion. Open and distance learning constitutes an educational ecosystem shaped by pedagogy, access, interaction, and institutional capacity, rather than mere technology-based content delivery. Persistent gaps include limited longitudinal evidence, underdeveloped research on family mediation, scarce child-centered design studies, and the absence of an integrated conceptual framework.